Analytical Procedures for the Evaluation of Infrastructural Measures for Increasing the Capacity of Railway Lines - Bulková, Zdenka; Gašparík, Jozef; Mašek, Jaroslav; Zitrický, Vladislav (Sustainability, 2022)
The issues that determine the capacity of railway infrastructure are topical in situations that are reaching operating limits. According to the objectives of the European transport policy, it is assumed that up to 30% of road freight over 300 km should shift to other modes such as rail or waterborne transport by 2030. The transport system should become more competitive and efficient in the use of resources. This places high demands on the railway infrastructure, which is mainly operated in a mixed transport mode, with both passengers and freight. It is necessary to increase the capacity of these lines as a priority. The intent of this paper is to propose procedures that will simply and accurately determine the quantification of benefits for increasing the throughput performance of the line. For the initial estimates and assessments of investment measures, it is advantageous to use analytical methods to determine the throughput performance. The methodological approach for determining the throughput performance in the anticipated timetable and case study were approximated on the example of the rail freight corridor marked “Amber” that passes through Slovakia. Analytical procedures have been proposed according to the methodology used on the railways of Slovakia, and the quality issues were assessed using a new approach for determining the optimal and critical throughput performance. The mentioned procedures are advantageous for assessing infrastructural measures from the point of view of a railway infrastructure manager.